Ni-phyllosilicate structure derived Ni–SiO2–MgO catalysts for bi-reforming applications: acidity, basicity and thermal stability. Issue 6 (5th March 2018) - Ashok, J.; Bian, Z.; Wang, Z.; Kawi, S.
Abstract : In this work, Ni–SiO2 –MgO materials synthesized via Ni-phyllosilicate (PS) intermediates were explored for bi-reforming of methane (BRM) reaction. Abstract : In this work, Ni–SiO2 –MgO materials synthesized via Ni-phyllosilicate (PS) intermediates were explored for bi-reforming of methane (BRM) reaction. The influence of steam and reaction temperature was also investigated for the BRM reaction. Overall, the 15 wt% Ni–30 wt% SiO2 –55 wt% MgO (Ni–SiO2 –MgO[55]) catalyst maintained exceptional catalytic performance (CH4 and CO2 conversions were 80% and 60%, respectively) at 750 °C for 140 h with negligible carbon deposition and also showed a stable H2 /CO of 2.0. The best catalytic performance of the Ni–SiO2 –MgO[55] catalyst is attributed to its enhanced basicity strength, reasonable moderate acidity strength and structural stability during high temperature reforming reaction. The formation and presence of Ni–Mg-containing phyllosilicates in fresh and reduced catalysts respectively was confirmed by TEM images and XRD analysis. The T max of around 750 °C in TPR profiles of Ni/SiO2 –MgO catalysts further confirms the strength of interactions between Ni and SiO2 –MgO support species.